Constructing Environmental Issues in Nickel Mining Raja Ampat: Ecolinguistic Analysis - Fajriani Fitri; Merry Andriani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This research analyzes how environmental discourse is constructed in Greenpeace Indonesia's Instagram posts captions discussing nickel mining issues in Raja Ampat. This research also combines Systematic Functional Linguistics (SFL) particularly the transitivity system and an ecolinguistic perspective by using a descriptive qualitative approach. Source data from eight selected captions on Greenpeace Indonesia Instagram. The Findings show the utterances in captions in Greenpeace Instagram frames nickel mining as an active threat through material processes, while Raja Ampat is represented as a high-value entity under threat through attributive relational processes. Participants establish a power hierarchy in which the mining industry emerges as the actor, nature as the victim, and the public as the potential protector. Circumstance elements function to reduce psychological distance and create a sense of urgency. This research concludes that Greenpeace's digital campaigns not only describe environmental issues but also construct moral narratives that raise awareness and encourage action. This research highlights the role of language as a tool for transforming environmental discourse.